Hubungan Pola Asuh, Pemberian Asi Eksklusif, dan Riwayat Infeksi dengan Kejadian Stunting di Wilayah Kerja Puskesmas Kebun Tebu Lampung Barat - Ernawati Ernawati; Ana Mariza; Wayan Aryawati (Universitas Malahayati Lampung, 2025)
ABSTRACT Stunting remains a health issue that requires attention. Stunting data in West Lampung Regency in 2021 was 22.7%. The prevalence of stunting at Kebun Tebu Public Health Center in West Lampung is high, reaching 27.1%. The impact of stunting on toddlers includes metabolic disorders, infections and immunity issues, digestive system disturbances, neural development and intelligence effects, socioeconomic implications, and health risks. The purpose is To understand the relationship between parenting patterns, exclusive breastfeeding, and history of infections with the occurrence of stunting. Methods in This study was quantitative design, utilizing an analytical survey design with a cross-sectional time approach. The population for this research consisted of all mothers with toddlers in the working area of Kebun Tebu Public Health Center in West Lampung, totaling 193 individuals. The sampling technique employed is proportional random sampling. Chi-square test is used for statistical analysis. Result is The statistical test results showed that variable parenting patterns get a p-value = 0.034, and OR = 2.308, exclusive breastfeeding p-value = 0.000, and OR = 6.369, and history of infectious diseases (p-value = 0.000, and OR = 5.995), and the occurrence of stunting. Conclusion is The research findings indicated a relationship between parenting patterns, exclusive breastfeeding, history of infectious diseases, and the occurrence of stunting. Suggestion: hoped that healthcare professionals enhance efforts to improve the nutritional status of toddlers through supplementary feeding and provide education on exclusive breastfeeding and Early Initiation of Breastfeeding (EIB) for mothers starting from pregnancy. Keywords: Parenting Patterns, Exclusive Breastfeeding, History of Infections, Stunting ABSTRAK Stunting hingga saat ini masih menjadi masalah kesehatan yang perlu diperhatikan. Data stunting di Kabupaten Lampung Barat tahun 2021 yaitu 22,7%. Prevalensi stunting di Puskesmas Kebun Tebu Lampung Barat cukup tinggi yaitu 27,1%. Dampak stunting bagi balita meliputi gangguan metabolik, infeksi dan imunitas, sistem digestif/ pencernaan, dampak perkembangan saraf dan kecerdasan, sosial ekonomi, serta risiko kesehatan. Tujuan penelitian ini Diketahui hubungan pola asuh, pemberian ASI eksklusif, dan riwayat infeksi dengan kejadian stunting. Jenis penelitian ini adalah kuantitatif. Rancangan survey analitik dengan pendekatan waktu cross sectional. Populasi dalam penelitian ini adalah seluruh ibu yang memiliki balita di Wilayah Kerja Puskesmas Kebun Tebu Lampung Barat, dengan jumlah 193 orang, dan teknik sampling proportional random sampling. Uji stastistik menggunakan uji chi-square. Hasil uji statistik variabel pada pola asuh orangtua diperoleh p-value = 0,034, dan OR = 2,308, pemberian ASI eksklusif p-value = 0,000, dan OR= 6,369, dan riwayat penyakit infeksi p-value = 0,000, dan OR= 5,995. Kesimpulan yaitu Hasil penelitian diperoleh ada hubungan pola asuh orangtua, pemberian ASI eksklusif, dan riwayat penyakit infeksi dengan kejadian stunting. Saran dalam penelitian ini diharapkan tenaga kesehatan dapat meningkatkan upaya perbaikan status gizi balita dengan pemberian makanan tambahan dan penyuluhan ASI eksklusif dan Inisiasi Menyusui Dini (IMD) bagi ibu sejak masa kehamilan. Kata Kunci: Pola Asuh, Pemberian ASI Eksklusif, Riwayat Infeksi, Stunting